Does trading mechanism shape cross-market integration? Evidence from stocks and corporate bonds on the Tel Aviv Stock Exchange - Hadad, Elroi (2025)
Purpose: This study investigates the influence of trading mechanisms on cross-market integration between stocks and corporate bonds on the Tel Aviv Stock Exchange (TASE) during the COVID-19 crisis. Unlike the worldwide practice of trading corporate bonds on an over-the-counter (OTC) market, TASE uses a limit-order-book (LOB) for both stocks and bonds, potentially creating unique volatility dynamics through direct information spillover. We analyze the volatility dynamics and spillover effects between TASE’s stock and corporate bond markets. Design/methodology/approach: We employ an exponential general autoregressive conditional heteroskedastic (EGARCH)(1,1) model to assess the impact of stock market fear, measured by implied volatility, on Tel-Bond 20 Index returns and volatility. A bivariate diagonal Baba-Engle-Kraft-Kroner (BEKK) model is also applied to capture time-series integration and cross-volatility spillovers between the TA-35 Index (stocks) and the Tel-Bond 20 Index (corporate bonds), especially during financial stress. Findings: The EGARCH model reveals a significant contagion effect, with increased stock market fear lowering corporate bond returns and increasing bond volatility. It also indicates a leverage effect, where negative shocks disproportionately amplify bond volatility. Diagonal BEKK results confirm strong cross-market volatility persistence, especially during crises, highlighting substantial financial contagion between stocks and bonds in TASE. While TASE’s market design improves the overall market quality, these findings underscore the LOB trading mechanism in facilitating financial contagion and systemic risk. Practical implications: The LOB trading in TASE facilitates direct information flow, intensifying volatility spillover and cross-market integration, with the degree of integration fluctuating based on market conditions. Investors and managers should consider alternative hedging strategies during volatile periods, as stock market sentiment significantly impacts bond stability. Regulators should assess how trading mechanisms affect market integration and risk, especially during periods of distress. Originality/value: This study offers new insights into how trading mechanisms influence cross-market dynamics, contributing to the literature on market design and financial contagion.